Magnitude and associated factors of perceived stress and its consequence among undergraduate students of Salale University, Ethiopia: cross-sectional study. Issue 10 (26th November 2021) - Amhare, Abebe Feyissa; Jian, Lei; Wagaw, Lealem Minwuyelet; Qu, Chengjuan; Han, Jing
ABSTRACT: Excessive stress may have a negative impact on students' performance and learning ability. The aim of this study is to assess the magnitude and associated factors of perceived stress and its consequences among undergraduate students at Salale University, Ethiopia. A self-administered cross-sectional study has been conducted among 421 students of Salale University from April 1 st to May 30 th, 2018. Multiple linear regressions and Spearman's rank correlation were applied. The overall response rate is 95.49 %. The mean perceived stress score (PSS-14) was 29.97 (standard deviation =7.48). Spearman correlation test has shown that perceived stress is significantly but negatively correlated with grade point average [rs = -0.25 (-0.334 – -0.153)] and year of studies [rs = -0.13 (-0.232 – -0.032)]. Increased perceived stress indices are significantly associated with female gender (P < 0.001), grade point average (P < 0.01), academic stressors (P < 0.01), and psychosocial stressors (P < 0.01). Mean of PSS-14 was high among health science students (31.42 ± 9.37) than agricultural (30.78 ± 7.69) and business students (28.04 ± 5.43), however, there were no statistically significant differences. These findings are sufficient to allow a large-scale study to further help better understanding the stress-vulnerability factors of undergraduate students.